FINANCIAL LITERACY ON THE PERFORMANCE OF COFFEE MSMEs IN SOUTH JAKARTA - Ferli, Ossi; Budhijana, R Bambang; Putra, Rama Aldian; Widagdo, Riedmen Gifar; Daulay, Muhammad Irfan (Universitas Nusa Cendana, 2025)
Micro, small, and medium enterprises (UMKM) are currently one of the supporting factors for the economy in Indonesia. The development of the coffee industry in Indonesia has grown very significantly from year to year. The transition from MSME shops to franchise businesses has been observed. However, good financial knowledge or literacy is also a factor that determines success in a business. Based on this, this research was conducted to examine the relationship between financial knowledge, financial attitudes, and financial behavior on the performance of MSMEs. The results of this research show that financial knowledge encompasses a positive relationship with the execution of MSMEs. Financial attitudes and financial behavior have no influence on MSME performance. And based on simultaneous testing, financial knowledge, financial attitudes, and financial behavior have a positive effect on the performance of MSMEs. Keywords: Financial Knowledge; Financial Attitude; Financial Behavior; UMKM; Performance